1977
DOI: 10.1139/f77-224
|View full text |Cite
|
Sign up to set email alerts
|

Limnological Characteristics of Ontario Lakes in Relation to Associations of Walleye (Stizostedion vitreum vitreum), Northern Pike (Esox lucius), Lake Trout (Salvelinus namaycush), and Smallmouth Bass (Micropterus dolomieui)

Abstract: Commonest lake types of the 15 combinations of four fish species (walleye, Stizostedion vitreum vitreum; northern pike, Esox lucius; lake trout, Salvelinus namaycush and smallmouth bass, Micropterus dolomieui) were walleye–pike (22%), pike "only" (19%), lake trout "only" (16%) and smallmouth bass "only" (10%). Lake trout–walleye and lake trout–walleye–smallmouth bass types were extremely rare. Lake depth and area were variables of greatest significance in distinguishing lake types by discriminant analysis. Cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 0 publications
3
42
0
Order By: Relevance
“…In temperate North America, variables describing biotic, abiotic and lake isolation conditions have been frequently identified as important factors shaping fish species richness and community composition (e.g., Johnson et al 1977;Harvey 1975Harvey , 1978Harvey , 1981Tonn and Magnuson 1982;Eadie et al 1986;Harvey 1989, 1993;Jackson et al 1992;Matthews and Robison 1998). The results from our study indicate a strong association between fish community composition and factors related to lake morphology, but not water chemistry, for all study lakes.…”
Section: Discussionsupporting
confidence: 46%
“…In temperate North America, variables describing biotic, abiotic and lake isolation conditions have been frequently identified as important factors shaping fish species richness and community composition (e.g., Johnson et al 1977;Harvey 1975Harvey , 1978Harvey , 1981Tonn and Magnuson 1982;Eadie et al 1986;Harvey 1989, 1993;Jackson et al 1992;Matthews and Robison 1998). The results from our study indicate a strong association between fish community composition and factors related to lake morphology, but not water chemistry, for all study lakes.…”
Section: Discussionsupporting
confidence: 46%
“…The assemblage definition based on the dominance of species (Echelle et al, 1972;Johnson et al, 1977;Ryder and Kerr, 1978;Matthews, 1998) was supported by the data from this study as well as others conducted in the European temperate zone (Kruk, 2007a;Kruk et al, 2007). We could not find any significant impact of impoudment on differentiation and numbers of assemblages except for the clearly separated assemblage distingushed on the basis of samples collected in the Furnas Stream, but only from samples collected in the post-impoudment period.…”
Section: Discussionsupporting
confidence: 86%
“…In contrast to numerous published lake classifications (e.g. HAEMPEL, 1930;BAUCH, 1963;JOHNSON et al, 1977;TONN and MAGNUSSON, 1982;DOLMAN, 1990;SCHUPP, 1992;SPINDLER, 1997;ARGILIER et al, 2002a, b;TAMMI et al, 2002;MEHNER et al, 2005), which are based on the recent fish communities, we used the LFI = Lake type specific fish community-index; range = total number of lake groups in which a given species occurs; pi= occurrence probability of a fish species in one lake group.…”
Section: Discussionmentioning
confidence: 82%
“…For example, TONN and MAGNUSSON (1982) categorized Wisconsin lakes according to the number of fish taxa present. JOHNSON et al (1977) classified 2,500 Ontario lakes based on the combination of four major recreational fishes present in each lake and found that seven limnological factors predicted the lake type in which each species combination occurred. For Texas reservoirs DOLMAN (1990) used cluster analysis revealing five different groups based on species associations.…”
Section: Introductionmentioning
confidence: 99%